The Effect of Motivation and Work Environment on Employee Performance Mediated by Job Satisfaction in Employees of Sukajadi Banyuasin Regional General Hospital - Al Ahda Adawiyah; Oscar Jayanagara (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of motivation and work environment on employee performance at the Sukajadi Regional General Hospital, Banyuasin, South Sumatra, with job satisfaction as a mediator. In the context of health organizations, employee performance plays an important role in maintaining the quality of service. Using quantitative methods, this study explores the relationship between these variables through relevant data analysis. The results of the study show that motivation and work environment have a positive and significant influence on employee performance, and job satisfaction functions as a mediator that strengthens the relationship between motivation, work environment, and employee performance. This finding is expected to provide insight for the development of more effective management strategies in improving employee performance in the hospital environment.